2022
DOI: 10.3390/ijerph19052745
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Body Image Perception and Ideals: Analysis of Possible Determinants

Abstract: The study analyzed the differences between sexes in body image perception and body ideals to assess possible dissatisfaction and misinterpretation in the body image considered attractive for the other sex. Moreover, the influence of anthropometric traits and sports practice on body dissatisfaction and misjudgment was evaluated. Using a cross-sectional design, 960 Italian university students were investigated. Anthropometric characteristics were measured directly. Assessment of body image perception was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 74 publications
1
17
1
1
Order By: Relevance
“…Other previous analyses conducted on adults had shown small/medium associations between PA and BI [ 17 , 25 ], pointing to a stronger PA impact of PA on BID among young people, according to Bassett-Gunter et al [ 17 ]. In particular, the number of hours spent in sports activities was found to be a predictor of body dissatisfaction with a decrease in BID as the number of hours spent in sports activities increases [ 19 ]. In this review, a positive effect of sports training on BID was found in a study [ 42 ] carried out by a repeated measure design: a decrease in BID and changes in anthropometric measurements were evident after 12 weeks of soccer training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other previous analyses conducted on adults had shown small/medium associations between PA and BI [ 17 , 25 ], pointing to a stronger PA impact of PA on BID among young people, according to Bassett-Gunter et al [ 17 ]. In particular, the number of hours spent in sports activities was found to be a predictor of body dissatisfaction with a decrease in BID as the number of hours spent in sports activities increases [ 19 ]. In this review, a positive effect of sports training on BID was found in a study [ 42 ] carried out by a repeated measure design: a decrease in BID and changes in anthropometric measurements were evident after 12 weeks of soccer training.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have particularly emphasized BI in the female sex, due to its greater dissatisfaction and the prevalent desire to be thinner with significant differences between actual and ideal silhouettes [ 19 ]. The pattern in the two genders is indeed different with higher female body image dissatisfaction (BID), indicating the greater importance given by females to physical appearance compared to males [ 19 ]. The relationship between body dissatisfaction and BMI was found to be linear in females [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…These recommendations are highly relevant since there is simultaneously a worldwide prevalence of physical inactivity and obesity. Indeed, the current sedentary lifestyle is one of the main causes of overweight/obesity [ 3 , 4 ], and this results in a high prevalence of dissatisfaction with the perceived body image (BI) because of the ideal of body thinness prevalent in Western societies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite overweight and obesity having metabolic effects, as well as causing changes in the pharmacodynamics of medications, our results also suggest they are associated with low-moderate adherence only in women. We might explain this gender-differential finding as a consequence of women having a poor body self-perception as BMI increases [ 38 ], and in turn, such self-perception might be associated with poor medication adherence [ 39 ]. BMI extracted from physical examination in women seems to be valuable predictor regarding medication use.…”
Section: Discussionmentioning
confidence: 99%